2015
DOI: 10.4103/0973-029x.174615
|View full text |Cite
|
Sign up to set email alerts
|

Primary intraosseous squamous cell carcinoma in odontogenic keratocyst: A rare entity

Abstract: Squamous cell carcinoma (SCC) arising from the wall of an odontogenic cyst (also known as primary intraosseous carcinoma) is a rare tumor which occurs only in jaw bones. This tumor was first described by Loos in 1913 as a central epidermoid carcinoma of the jaw. Primary intraosseous carcinomas (PIOC) may theoretically arise from the lining of an odontogenic cyst or de novo from presumed odontogenic cell rests. According to the new histological classification of tumors of the World Health Organization, odontoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The treatment of choice to such tumors is surgery and/or radiation therapy [1,4]. Thomas that very poor prognosis of two year survival rate was seen in patients having PIOSCC [4], this was in common with the present case where the patient had a recurrence twice and his condition deteriorated after the second recurrence and he passed away a month later.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The treatment of choice to such tumors is surgery and/or radiation therapy [1,4]. Thomas that very poor prognosis of two year survival rate was seen in patients having PIOSCC [4], this was in common with the present case where the patient had a recurrence twice and his condition deteriorated after the second recurrence and he passed away a month later.…”
Section: Discussionsupporting
confidence: 83%
“…PIOSCC was described to be a rare finding within jaw bones [1]. Bodner et al conducted a retrospective study of 116 cases of PIOSCC between 1938 and 2010 and reported that only 16 cases of these aroused from OKC [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human medicine, PIOSCC is a rare oral tumor, representing less than 2% of all oral SCCs in people [ 8 10 ]. The majority of PIOSCCs arise from other benign odontogenic tumors or cysts, while solid de novo type PIOSCC is extremely rare [ 11 , 12 ]. Although PIOSCC has not yet been described in cats, in the clinical case presented here, the radiographic and microscopic features were very similar to those described for human solid type PIOSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was later referred to an Oncology center. Associating the histopathological and imaging features[ 1 2 ] a diagnosis of primary intraosseous SCC (PIOSCC) was made.…”
mentioning
confidence: 99%